Effect of Salt on Auxin-Induced Acidification and Growth by Pea Internode Sections - Terry, Maurice E. (1981)
The capacity of excised internode sections of pea to grow and secrete protons in response to indoleacetic acid (IAA) and Ca(2+) and K(+) treatments was examined. By incubating unpeeled and unabraded sections in rapidly flowing solutions, it was shown that acidification of the external medium in the presence or absence of IAA is dependent on the presence of Ca(2+) and K(+). Similar results were obtained when unpeeled and unabraded sections were incubated in dishes with shaking. When peeled or abraded sections were incubated with shaking in IAA, H(+) release was also dependent on the presence of Ca(2+) and K(+). The release of H(+) from sections incubated in Ca(2+) and K(+) is not caused by displacement of H(+) from binding sites in the cell wall. Rather, the release of protons from sections is temperature dependent, and it is concluded that this is a metabolically linked process. Although Ca(2+) and K(+) are essential for the release of H(+) from isolated stem sections of peas, these cations do not influence elongation. Despite the large increase in proton release induced by Ca(2+) and K(+) either in the presence or absence of auxin, growth in the presence of these ions was never greater than it was in their absence. Furthermore, cations do not affect the neutral sugar or uronic acid composition of the solution which can be centrifuged from isolated sections. As is the case for growth, an increase in the neutral sugar and uronide composition of the cell wall solution is dependent only on IAA. It is concluded that IAA-induced growth of pea stem sections is independent of the secretion of protons.